PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIVE TIPE TEAM GAMES TOURNAMET (TGT) UNTUK MENINGKATKAN KOLABORASI SISWA KELAS V DI SDN 134 PANORAMA KOTA BANDUNG - Lucia Christin Sembiring; Sandi Budi Iriawan; Enung Nurlaela (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
The learning process implemented so far shows a lack of collaboration skills among fifth-grade students, who tend to prefer working on tasks individually. This issue is caused by students' habitual use of smartphones and a lack of interaction with classmates. As a result, there is a lack of collaborative interaction among the students. This study aims to determine the improvement in collaboration among students during group discussions in the Pancasila Education subject in class V A at SDN 134 Panorama using the Team Games Tournament (TGT) cooperative learning model. This research is a Classroom Action Research involving 27 students from class V B during the second semester of the 2023/2024 academic year. The research process consists of two cycles. Data collection was conducted through observation sheets and documentation. The average percentage of student collaboration in group discussions increased from the first cycle (66.05%) to the second cycle (85.21%). Therefore, the study concludes that the use of the Team Games Tournament (TGT) cooperative learning model successfully enhances student collaboration.